The Vertical Orchidarium a multi-level research and exhibition facility for Philippine endemic and indigenous orchids - Cagang, Mary Camille I.; Araneta, Maureen Anne (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
The Orchid has been one of the most favorite backyard flower not only in the Philippines but for the most part of the world. It is adored by many flower enthusiasts because of its uniqueness and vast variety. The Philippines has been admired by many orchid enthusiasts and researchers around the world because of its rich orchid varieties. But the varieties of this wonder flower which can only be found in the Philippines are slowly becoming extinct because of deforestation and relentless hybridization with foreign orchid species. This design thesis aims to address the dilemma of the Philippines is facing due to the threatened status of its endemic orchids by providing a facility that will showcase the beauty and importance of orchids and help in conserving and propagating them. The Philippines is quite aware of the status of the Philippine endemic and indigenous orchids. There are agencies dedicated to the conservation of Philippine endemic orchids and private orchid societies willing to devote time and money just to preserve and conserve Philippine endemic orchids such as The Philippine Orchid Society. But without the proper facility and venue, they wouldn't be able to reach out further to the masses to promote awareness and to share their knowledge about the proper care and importance of orchids in the Philippine culture. Through publications done by mostly foreign orchid enthusiasts who have been scouting the islands of the Philippines to find new species and other researches done in this design thesis, the role of the orchid in the Philippine culture has been further solidified. It has been found that orchids also had other uses even during the time of the early Filipinos, such as medicine and material for arts and crafts. These are just few of the things that not every Filipino knows about. In addition, it was realized through the researches done how delicate and complex orchids are which can be compared to Filipinos and may very well indeed be a part of the Filipino identity.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Vertical Orchidarium